2021
DOI: 10.1007/978-1-0716-1433-4_10
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Proapoptotic Protein Trafficking to and from Mitochondria

Abstract: Mitochondria play a key role in cell death and its regulation. The permeabilization of the outer mitochondrial membrane which is mainly controlled by proteins of the BCL-2 family, is a key event that can be directly induced by p53 and results in the release of pro-apoptotic factors to the cytosol, such as cytochrome c, second mitochondria derived activator of caspases/direct inhibitor-of-apoptosis (IAP) binding protein with low p I (SMAC/Diablo), Omi serine protease (Omi/HtrA2), apoptosis inducing factor (AIF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Mitochondria play a key role in cell death and its regulation, and Bcl-2 family proteins control mitochondrial outer membrane permeability by regulating membrane potential ( 34 ). The imbalance of Bcl-2 family expression results in the release of proapoptotic factors into the cytoplasm, thereby inducing apoptosis ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria play a key role in cell death and its regulation, and Bcl-2 family proteins control mitochondrial outer membrane permeability by regulating membrane potential ( 34 ). The imbalance of Bcl-2 family expression results in the release of proapoptotic factors into the cytoplasm, thereby inducing apoptosis ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…After being regulated by apoptosis-related gene B cell lymphoma-2 (Bcl-2), the Caspase family can directly destroy cell structure and induce mitochondrial apoptosis (Häcker, 2018). Related studies have found that Smac/DIABLO and Omi/HtrA2 are present in mitochondria, which can be released from mitochondria into cytoplasm when the cell structure is disrupted, thus serving as a marker of mitochondrial apoptosis (Grosser et al, 2021;Vega-Naredo et al, 2021). Toll-like receptor 4 (TLR4) signalling is a classical pathway of polysaccharide mediated immunoregulation (Li et al, 2022;Zhao et al, 2022).…”
Section: Immunomodulatory Activitymentioning
confidence: 99%